Association of postoperative covert stroke and cognitive dysfunction among elderly patients undergoing non-cardiac surgery: protocol for a prospective cohort study (PRECISION study). Issue 1 (6th January 2020) - Cui, Qianyu; Wang, Dexiang; Zeng, Min; Dong, Jia; Jin, Hailong; Hu, Zhengfang; Zhang, Yuan; Peng, Yuming; Han, Ruquan
Abstract : Introduction: The incidence of covert stroke and cognitive dysfunction has gradually increased due to an ageing population. Recently, a prospective cohort study reported perioperative covert stroke was associated with an increased risk of postoperative cognitive dysfunction (POCD) 1 year after non-cardiac surgery. However, the mechanism remains unclear. Methods and analysis: This is a prospective observational trial aiming to investigate the cumulative incidence of perioperative covert stroke and test the hypothesis that perioperative covert stroke associates with POCD in elderly patients undergoing non-cardiac and non-neurological surgery. Data on risk factors, brain MRI, cognitive function evaluation and serum immune-inflammatory cytokines will be collected and analysed. Ethics and dissemination: Ethical approval has been granted by the Medical Ethics Committee of Beijing Tiantan Hospital, Capital Medical University (reference number: KY2017-027-02). The results of this study will be disseminated through presentations at scientific conferences and publication in scientific journals. Trial registration number: NCT03081429 .